2010
DOI: 10.2139/ssrn.1600221
|View full text |Cite
|
Sign up to set email alerts
|

Advertising Bans and the Substitutability of Online and Offline Advertising

Abstract: We examine whether the growth of the internet has reduced the effectiveness of government regulation of advertising. Specifically, we combine variation in state and local regulation of offline alcohol advertising with data from field tests that randomized exposure to online advertising for 275 different online advertising campaigns to 61,580 individuals. People are 8 percent less likely to say that they will purchase an alcoholic beverage in states that have alcohol advertising bans compared to states that do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 45 publications
0
12
0
Order By: Relevance
“…16 The distribution of advertising rates per reader is heavily skewed so we employ its natural logarithm as our dependent variable.…”
Section: Regression Specificationmentioning
confidence: 99%
See 3 more Smart Citations
“…16 The distribution of advertising rates per reader is heavily skewed so we employ its natural logarithm as our dependent variable.…”
Section: Regression Specificationmentioning
confidence: 99%
“…Zentner (2011) shows that advertising budgets in traditional media have decreased in countries with higher rates of Internet use. In addition, two recent papers by Tucker (2011c and2011d) conclude that the Internet is a substitute to offline advertising, although they do not specifically examine targeted advertising. Their results suggest that online advertising for certain goods is either more effective or higher priced in those jurisdictions where offline advertising is not permitted; thereby indicating that offline and online channels for these goods are substitutes.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…They used data from the books sold on Amazon, which were the top sellers in 1497 local bookstores in America. Goldfarb et al [4] analyzed the substitution between the online and offline advertising markets. The authors showed that online advertising substitutes the offline advertising, but the opposite was not true.…”
Section: Introductionmentioning
confidence: 99%